Piezo1 dictates K + homeostasis through coordinated regulation of the ubiquitin ligase Kelch-like 3 in RBCs and the kidney - Kenichi Ishizawa; Ken Kaseda; Wataru Fujii; Yoshihiro Tomomitsu; Daigoro Hirohama; Osamu Yamazaki; Yuta Kochi; Shigeru Shibata (Proceedings of the National Academy of Sciences, 2026)
The maintenance of potassium (K + ) balance is a fundamental biological process involving multiple tissues. However, the roles of intertissue crosstalk in K + homeostasis remain poorly understood. Here, we demonstrate that the mechanosensor Piezo1 dictates extracellular K + homeostasis by orchestrating the ubiquitin ligase Kelch-like 3 (KLHL3) activity in red blood cells (RBCs; erythrocytes) and the kidney. Genetic variants within KLHL3 with expression quantitative trait locus effects are associated with altered RBC parameters, and CRISPR-generated KLHL3 knock-in (KLHL3-KI) mice carrying a nonphosphorylatable Ala substitution at its activation site (Ser433) reveal that KLHL3 regulates erythrocyte volume by modulating with-no-lysine 1 (WNK1). In wild-type, but not in KLHL3-KI, erythrocytes, Piezo1 activates KLHL3 through Ser433 dephosphorylation, reducing WNK1 abundance and intracellular K + content—a physiologically adaptive response to hypo-osmotic stress. KLHL3-KI mice exhibit hyperkalemia and reduced fractional K + excretion, accompanied by elevated WNK levels and reduced renal outer medullary K + (ROMK) abundance in collecting ducts of the kidney. Single-cell transcriptomics confirm coexpression of Piezo1 and KLHL3 in these segments, where Piezo1 regulates WNK abundance through KLHL3-Ser433 dephosphorylation. In human genetic studies of 200,367 UK Biobank participants, the PIEZO1 missense variant rs563555492 (p.L2277M) is independently associated with lower urinary K + . Piezo1-mediated WNK1 regulation is abolished in human kidney cells expressing Piezo1 L2277M . Causal role of Piezo1 in regulating K + excretion and ROMK was confirmed in vivo. These findings identify Piezo1–KLHL3 interaction as a key intertissue signaling mechanism between erythrocytes and the kidney that governs K + homeostasis, and suggest this pathway as a therapeutic target for dyskalemia.